"If you don't find anything, you can't eat" – Mining livelihoods and income, gender roles, and food choices in northern Guinea. (March 2021) - Stokes-Walters, Ronald; Fofana, Mohammed Lamine; Songbono, Joseph Lamilé; Barry, Alpha Oumar; Diallo, Sadio; Nordhagen, Stella; Zhang, Laetitia X.; Klemm, Rolf D.; Winch, Peter J.
Abstract: Artisanal and small-scale mining (ASM) continues to grow as a viable economic activity in sub-Saharan Africa. The health and environmental impacts of the industry, notably linked to the use of potentially toxic chemicals, has been well documented. What has not been explored to the same extent is how pressures associated with ASM affect food choices of individuals and families living in mining camps. This paper presents research conducted in 18 mining sites in northern Guinea exploring food choices and the various factors affecting food decision-making practices. Two of the most influential factors to emerge from this study are income variability and gender roles. Results from this study suggest that through artisanal mining, women have the opportunity to earn a larger income that would otherwise be unavailable through agriculture. However, this benefit of potentially earning a larger income is often reduced or constrained by existing gender roles both at the mines and in the home, such as disparity in pay between men and women and increased pressures on women's time. This limits the potential benefit to household food decision-making that could have been gained from higher income. These results do not seek to establish one livelihood as superior; rather, they demonstrate that even when presented with opportunities to earn higher incomes, women still face many of the same barriers and challenges that they would in other economic activities. Additionally, while work and time demands on women change upon arrival in the mining camps, existing gender roles and expectations do not, further restricting women's decision-making capacity. Highlights: Artisanal mining brings greater earnings that miners can use to acquire food. Time constraints linked to mining, as well as domestic tasks, limit food choice. Unequal payment for mining work further restrict women's food choices. Income instability significantly impacts caregiver food decision-making abilities.